Isolasi dan Identifikasi Bakteri Penyebab Penyakit pada Ikan Nila (Oreochromis niloticus) di Desa Tatelu Kecamatan Dimembe Kabupaten Minahasa Utara - Watugigir, Gerfindo Y. G; Rayer, Debby J. J.; Lawalata, Helen J; Watung, Fernando A; Rampengan, Mercy M. F (LPPM Politeknik Saint Paul Sorong, 2024)
Tilapia is a freshwater animal that is always in contact with the aquatic environment so that it is easily infected by bacteria through water. This study aims to identify the types of bacteria that cause diseases that attack Tilapia (Oreochromis niloticus) kept in Dimembe District, North Minahasa Regency. This study uses a descriptive exploratory research method. The results of the study found sixteen isolates and identified them as bacteria that cause Tilapia disease in North Minahasa Regency, including Aeromonas sp. (4 isolates), Plesiomonas sp. (5 isolates), and Enterobacter sp. (1 isolate). based on morphological characteristics (colonies and bacterial cells) and biochemical (catalase, oxidase and motility tests). It was found that periodic and continuous fish disease surveillance is needed to monitor the spread of fish diseases, especially Tilapia disease in North Minahasa